Prevalence, risk factors and complications of post-implantation syndrome after endovascular abdominal aortic aneurysm exclusion: a systematic review - Gonçalo Miguel Santos e Araújo (2021)
INTRODUCTION Despite the proven benefits of endovascular aneurysm repair (EVAR), it has been demonstrated that such procedures can trigger a systemic inflammatory response, named post-implantation syndrome (PIS). The etiology and prognostic implications of this condition have been described in the literature, with conflicting results. Through this work, we aim to review the prevalence, risk factors and complications of post-implantation syndrome after EVAR. EVIDENCE ACQUISITON A literature search was performed on MedLine, Scopus and Web of Science databases, which returned 41 studies. Nineteen studies were included. Data were extracted using piloted forms, and, if necessary, authors were contacted to obtain further information. EVIDENCE SYNTHESIS In this systematic review, 19 studies reporting significant evidence about prevalence, risk factors and complications of PIS after EVAR were analyzed. PIS prevalence ranged from 11.4% to 44%, with four different definitions of PIS applied in sixteen different studies where they were reported. The only variable found to be systematically associated with the occurrence of PIS was polyester stentgraft fabric. Seven studies reported such findings, with PIS prevalence ranging from 14%-56.1% for patients treated with polyester grafts comparing to 0%-17.9% for those treated with ePTFE grafts. Regarding PIS-related complications, seven studies reported an association between PIS and worse outcomes after intervention. Out of these, three reported PIS to be associated with a significant higher risk of post-operative cardiovascular complications during the first 30 days after surgery, while one also determined an higher risk of complications in the first year of follow up. Five studies demonstrated that PIS increases length of hospital stay while one reported lower quality of life for patients with this condition. CONCLUSION Prevalence of PIS varies greatly in literature due to the absence of standardized diagnostic criteria. Some studies report an association between PIS and short-term as well as long-term adverse events, including MACE. Nonetheless, current evidence is scarce and no conclusion can be strongly drawn.